2021
DOI: 10.3168/jds.2020-18955
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Molecular markers for epithelial cells across gastrointestinal tissues and fecal RNA in preweaning dairy calves

Abstract: The objective of this study was to compare the transcription of gene markers for gastrointestinal (GI) epithelial cells, including fatty acid binding protein 2 (FABP2) and cytokeratin 8 (KRT8), and tight junction complex genes (TJP1, CLDN1, CLDN4) in fecal RNA against several GI tract tissue sections in dairy calves. Eight healthy Jersey calves were euthanized at 5 wk of age, and postmortem samples were collected from rumen, duodenum, jejunum, ileum, large intestine, cecum, and feces for total RNA isolation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Tis characteristic has also been reported for other types of organoids such as the human and murine liver [45,46]. Te highest level of FABP2 expression was in ileal organoids followed by jejunal and large intestinal organoids in this study, which is in accordance with a previous report that evaluated gene expression in various locations of intestinal tissues collected from Jersey calves [47]. Indistinguishable levels of Muc2 gene expression across jejunal, ileal, colonic, and rectal organoids was also in agreement with a previous study using tissues collected from 4-year-old cows [48].…”
Section: Discussionsupporting
confidence: 92%
“…Tis characteristic has also been reported for other types of organoids such as the human and murine liver [45,46]. Te highest level of FABP2 expression was in ileal organoids followed by jejunal and large intestinal organoids in this study, which is in accordance with a previous report that evaluated gene expression in various locations of intestinal tissues collected from Jersey calves [47]. Indistinguishable levels of Muc2 gene expression across jejunal, ileal, colonic, and rectal organoids was also in agreement with a previous study using tissues collected from 4-year-old cows [48].…”
Section: Discussionsupporting
confidence: 92%
“…This is relevant to the current study in that Rosa et al [ 12 , 13 ] demonstrated that even under nondiarrheic conditions, RNA isolated from neonatal dairy calf feces is derived from a considerable number of IECs as evidenced by mRNA expression of KRT8 . This held true in our study in that KRT8 mRNA abundance exceeded that from other genes of interest, suggesting that a considerable amount of fecal RNA originated from IECs.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to disrupting tight junction proteins, nitric oxide is implicated in the induction of enterocyte apoptosis and an accelerated rate of intestinal epithelial cell (IEC) shedding potentially exceeding the rate of IEC production and disturbing intestinal homeostasis [42,43]. This is relevant to the current study in that Rosa et al [12,13] demonstrated that even under nondiarrheic conditions, RNA isolated from neonatal dairy calf feces is derived from a considerable number of IECs as evidenced by mRNA expression of KRT8. This held true in our study in that KRT8 mRNA abundance exceeded that from other genes of interest, suggesting that a considerable amount of fecal RNA originated from IECs.…”
Section: Plos Onementioning
confidence: 87%
See 1 more Smart Citation